2005
DOI: 10.1080/0958519042000339552
|View full text |Cite
|
Sign up to set email alerts
|

Met expectations and supplies–values fit of Dutch young adults as determinants of work outcomes

Abstract: Many studies have shown that work outcomes, such as job satisfaction and turnover intentions, are affected by met expectations and the fit between the work values of an employee and the supplies offered by the organization. However, research that investigates their simultaneous effects on work outcomes is absent in the literature. This study examined the concurrent effects of met expectations and supplies-values (S-V) fit of Dutch young adults on job satisfaction and intention to leave. It was hypothesized tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
2

Year Published

2009
2009
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 47 publications
0
18
2
Order By: Relevance
“…Also, using values measured from three independent sources, another study failed to find sufficient evidence regarding the existence of value congruence (Knoppen, Dolan, Diez-Pinol, & Bell, 2006) and proposed focusing more on value incongruence in future research. Other studies reported that organizational commitment was affected mainly by personal and organizational values, the effect of value congruence being marginal (Verplanken, 2004), and that value congruence did not explain more variance than variance explained by the components alone (Taris, Feij, & van Vianen, 2005). In a Kenyan organizational context, it was found that it was the value itself, not its congruence, that explained more variance regarding job involvement (Nyambegera, Daniels, & Sparrow, 2001).…”
Section: Job Attitudesmentioning
confidence: 93%
“…Also, using values measured from three independent sources, another study failed to find sufficient evidence regarding the existence of value congruence (Knoppen, Dolan, Diez-Pinol, & Bell, 2006) and proposed focusing more on value incongruence in future research. Other studies reported that organizational commitment was affected mainly by personal and organizational values, the effect of value congruence being marginal (Verplanken, 2004), and that value congruence did not explain more variance than variance explained by the components alone (Taris, Feij, & van Vianen, 2005). In a Kenyan organizational context, it was found that it was the value itself, not its congruence, that explained more variance regarding job involvement (Nyambegera, Daniels, & Sparrow, 2001).…”
Section: Job Attitudesmentioning
confidence: 93%
“…In contrast, extrinsic motives refer to the strength of preferences for job features and outcomes that occur as a consequence of work, rather than as an integral part of the work process. Examples of extrinsic motives include compensation, benefits, and promotion (see Chang, Choi, & Kim, 2008; Johnson, 2001; Taris, Fey, & Van Vianen, 2005; Van der Velde, Fey, & Van Emmerik, 1998).…”
Section: Age and Motive‐related Factorsmentioning
confidence: 99%
“…Hom et al , 1999; Irving & Meyer, 1994), researchers continue to use the discrepancy between expected and delivered inducements (assessed with difference scores or direct measures) as an important predictor of employee reactions (e.g. Caligiuri, Phillips, Lazarova, Tarique, & Bürgi, 2001; Moser, 2005; Mueller, Iverson, & Jo, 1999; Naumann, Widmier, & Jackson, 2000; Taris, Feij, & Capel, 2006; Taris, Feij, & van Vianen, 2005). In doing so, the met expectations literature may be generating less than optimal guidance for organizations.…”
Section: Potential Problems Interpreting the Met Expectations Literaturementioning
confidence: 99%